An Experimental Investigation of Small Angle Scattering of (200-1500 keV) Gamma Rays - Ramanathan, Naganathasastrigal (My University, 1977)
Differential cross-sections for the small angle (2° - 10º) scattering of 1408.0, 1274.2, 1112.0, 1085.8, 964.0, 778.9, 443.9, 344.3 and 244.7 keV gamma rays from lead, tantalum, cadmium, copper, aluminum and carbon were measured experimentally employing a high resolution gamma ray spectrometer system. An attempt was made to separate the coherent and incoherent components of the scattered radiation. An empirical model was developed to generate the shape or energy distribution of the incoherently scattered gamma rays and was applied to extract these components where these were unresolved. Various correction factors for the coherent and incoherent components have been considered.
The experimental results for the coherent scattering in lead, tantalum, cadmium and copper were compared with the form-factor based numerical computations. Significant deviations have been observed and some of the possible causes are indicated. The present results are compared with the previous measurements, wherever available, on the basis of momentum transfer.
This work reports the first set of systematic measurements of the incoherent scattering cross-sections for small momentum transfers (1.0Åˉ¹ - 10.0Åˉ¹). The experimental incoherent scattering functions are found to be considera0bly lower than the theoretical values for the scatterers of high atomic number.
Keywords: Physics; Physics